Factors Affecting the Process of Role Transition from Nursing Student to Clinical Nurse: a Grounded Theory Study - F Rafii; M Sajadi Hezaveh; N Seyedfatemi; M Rezaei (Iran University of Medical Sciences, 2015)
Abstract   Background & Aim: Role transition from nursing student to clinical nurse is a sensitive stage in the nurses' professional life. Many factors affect role transition and could change its outcome. The present study was designed with the aim of exploring the factors affecting the process of transition from nursing student to clinical nurse using the experiences of both novice and experienced nurses.   Material & Methods: This study was conducted by grounded theory approach in educational hospitals affiliated to Tehran University of Medical Sciences. Data was generated by in-depth, semi-structured interviews. A total of 21 participants were recruited by purposeful and theoretical sampling. They included 17 new graduate nurses, two experienced nurses and two head nurses. According to grounded theory, data collection and analysis was performed simultaneously using constant comparative method.   Results: the study revealed that many factors affect the process of role transition from nursing student to clinical nurse. These factors were classified as micro and macro levels. Micro-level factors included pedagogic-educational support, characteristics related to head nurse and colleagues, newly graduate nurses' characteristics, and work place atmosphere. The macro-level factors included the perspective of society to nursing, physicians' rulership governing the medical centers, and nurses' employment regulations.   Conclusion: The findings of this study could create a new insight into thinking about factors effecting newly graduated nursing student' role transition on the commencement of their work and also create a basis for professional decisions. Recognition of these factors could help in planning and direction of the process towards positive outcomes. The findings could also be considered as a guide for managers, educational instructions, authorities and all the beneficiaries in nursing, in order to facilitate this process for newly graduated nurses.